Evaluation and increase of load capacity of on-load tap changing transformers for improvement of their regulating possibilities - Buslavets, Olga; Lezhniuk, Petro; Rubanenko, Olexander (Eastern-European Journal of Enterprise Technologies, 2015)
Among measures, aimed at reduction of electric energy losses, usage of the transformers for power flows correction in electric networks is recommended as the most efficient means of energy losses reduction during its transmission. The efficiency of this method considerably increases when the process of power flows optimal control is carried out in automatic mode. For this purpose automatic regulators and systems of automatic control of transformation ratios of the transformers with on load tap changing have been developed. However, electric energy losses reduction using optimal control of power flows in electric networks will become efficient only when technical states of the transformers and autotransformers, involved in the process of control must be satisfactory and their residual resource and current loading capacity must have certain reserve. For their determination it is necessary to create corresponding methods and means of on-line diagnostics of the transformers and autotransformers. It is obvious that they must use the possibility of modern hardware and software and be based on SMART GRID principles. Mathematical model of the forecast temperature of upper levels of oil has been developed, among other parameters, the given model takes into account the coefficient of residual resource of the coolers. For evaluation of technical state of the transformers cooling system the facilities of neuro-fuzzy models will be used, as a result, functional dependences between important factors are taken into consideration. Neuro-fuzzy model of the transformers loading capacity, depending on the resource coefficient of its cooling system has been developed. It is shown that maximum usage of transformers loading capacity, if it operates within automatic control system of electric energy system, is realized by means of the mechanism of establishment of the corresponding non-sensitivity zone of on-load tap champing operation. Coordination of transformers operation in the system of optimal control of power flows in EES is realized by setting parameters and non-sensitivity zones of SAC, determined taking into account loading capacity of the transformers.